1998
DOI: 10.1021/tx980163p
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nitrous Acid-Dependent Tyrosine Nitration and DNA Base Deamination by Flavonoids and Other Phenolic Compounds

Abstract: Exposure of tyrosine or DNA bases to acidic nitrite at low pH results in the nitration of tyrosine and the formation of base deamination products, respectively. At pH 1, hypoxanthine and xanthine are formed from the deamination of adenine and guanine, respectively, whereas under the same conditions, uracil is not detected. The yield of 3-nitrotyrosine derived from interaction of equimolar nitrite and tyrosine at pH 1 is approximately 50% of that obtained from equimolar peroxynitrite-tyrosine interactions at pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
60
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 31 publications
4
60
1
Order By: Relevance
“…It is notable that the use of EC detection provides ≈100 times greater sensitivity than that which can be obtained using UV/VIS absorption. Protein hydrolysis for the release of free 3-NT from proteins is performed under neutral conditions, minimizing the potential for artifactual nitration that may occur in acidified nitrite-containing solutions (Oldreive et al, 1998). When performed as described, the efficiency of protein 3-NT retrieval from crude extracts of cells and tissues routinely exceeds 85%.…”
Section: Quantification Of 3-nt In Proteins Using Hplc Separation Andmentioning
confidence: 99%
“…It is notable that the use of EC detection provides ≈100 times greater sensitivity than that which can be obtained using UV/VIS absorption. Protein hydrolysis for the release of free 3-NT from proteins is performed under neutral conditions, minimizing the potential for artifactual nitration that may occur in acidified nitrite-containing solutions (Oldreive et al, 1998). When performed as described, the efficiency of protein 3-NT retrieval from crude extracts of cells and tissues routinely exceeds 85%.…”
Section: Quantification Of 3-nt In Proteins Using Hplc Separation Andmentioning
confidence: 99%
“…These compounds, collectively referred to as green tea catechins polyphenols (GTPs), exhibit antioxidant properties as free radical scavengers, and recent epidemiological studies have shown that GTP compounds may reduce the risk of a variety of different diseases (10). Although the specific mechanisms of these protective effects remain unresolved, these findings have sparked intense interest in the potential therapeutic value of theses compounds in conditions associated with increased oxidative load (11)(12)(13)(14). Therefore, the present study was undertaken to investigate the impact of oral GTP on oxidative stress, inflammatory load, and neurobehavioral impairments in our animal model of SDB.…”
mentioning
confidence: 99%
“…The results suggest that quercetin and nitrite were competitively oxidized by the H 2 O 2 /MPO system and that the oxidation intermediates of nitrite also oxidized quercetin. It has been suggested that the H 2 O 2 /MPO system oxidizes nitrite (van der Vliet et al, 1997) and that polyphenols inhibit acidic nitritedependent nitration of tyrosine by scavenging nitrogen oxides (Oldreive et al, 1998). Quercetin was also oxidized by SPMN in the absence (Hirota et al, 2002) and presence of NaNO 2 (data not shown).…”
mentioning
confidence: 79%
“…The importance of the phenolics as antioxidants in the oral cavity is deduced from the report that polyphenols can scavenge reactive oxygen species generated by SPMN (Hirota et al, 2002). The importance is also deduced from the result that polyphenols can inhibit myeloperoxidase (MPO)-and acidic nitrite-dependent nitration of free tyrosine and tyrosine residues in proteins (Halliwell et al, 1999;van der Vliet et al, 1997;Oldreive et al, 1998;Oldreive & Rice-Evans, 2001) and can protect DNA bases against deamination by nitrous acid (Oldreive et al, 1998;Zhao et al, 2001). Furthermore, polyphenols can react with nitrogen oxides like nitric oxide (Haenen et al, 1997;Herencia et al, 2002;Paquay et al, 2000;van Acker et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation